A rare case of Pleuropulmonary blastoma type III with Immunohistochemical Study - Siddhi Gaurish Sinai Khandeparkar; Maithili Mandar Kulkarni; Bageshri P. Gogate; Chinmayee Sanjeev Dhavan (Indian Journal of Pathology and Microbiology)
Here we intend to document a rare case of PPB type III in a 2-year male presenting with an extensive tumor occupying the right hemithorax with immunohistochemical (IHC) study. Pleuropulmonary blastoma (PPB) is a rare variably aggressive, dysodontogenetic, childhood primary intrathoracic malignancy which in up to 25% of cases can be extrapulmonary with attachment to the parietal pleura. It is found in pediatric population under 5 years of age. It was initially proposed as a distinct entity by Manivel et al. in 1988. PPB is a proliferation of primitive mesenchymal cells that initially form air-filled cysts lined by benign-appearing epithelium (type I, cystic). Later on, the mesenchymal cells outgrow the cysts with formation of focal solid areas (type II, solid and cystic) and finally, mainly solid mass (type III, solid PPB).